Shared histological and immunohistological findings in two patients with generalized vitiligo associated with autoimmune atrophic gastritis - Fariba Ghalamkarpour; Muriel Cario André; Yvon Gauthier (Clinical Case Reports, 2022)
Abstract The prevalence of autoimmune atrophic gastritis (AAG) in vitiligo patients was estimated at about 15%. In both conditions, a release of specific antibodies and an autoimmune destruction of target cells (melanocytes in vitiligo, parietal cells (PC) in AAG) mediated by CD8‐T lymphocytes was demonstrated to perform a comparative histological study of vitiligo skin and AAG mucosa. In two patients with concomitant vitiligo and AAG, biopsies from the vitiligo lesions and gastric mucosa from corpus fundus were performed. Sections were immunostained with E‐cadherin, Coll IV, CD8, CD20, CD4 antibodies. The skin sections also were stained with HES, HMB45, MITF. Common histological findings were found in both diseases. Adhesivity impairment with down expression of E‐cadherin and Coll IV was objectivated. The protruding MITF+melanocytes and the detached PC were surrounded by an infiltrate including CD8 and CD4. CD8 was infiltrating the epidermis in close contact with the remaining melanocytes and the gastric glands around the remaining PC. In both diseases, the autoimmune process could be preceded by a detachment of either melanocytes in vitiligo or PC in AAG possibly in relation to an initial adhesivity impairment of these cells. Common autoimmune mechanisms could be suggested for both diseases.